2019
DOI: 10.3389/fpsyg.2019.00608
|View full text |Cite
|
Sign up to set email alerts
|

Evaluative Processing of Food Images: Longer Viewing for Indecisive Preference Formation

Abstract: The well-known gaze cascade hypothesis proposes that as people look longer at an item, they tend to show an increased preference for it. However, using single food images as stimuli, we recently obtained results that clearly deviated from the general proposal that the gaze both expresses and influences preference formation. Instead, the pattern of data depended on the self-determination of exposure duration as well as the type of evaluation task. In order to disambiguate how the type of evaluation determines t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…Interestingly, this notion of extra information integration under doubt is also compatible with other findings from our laboratory on the cognitive mechanisms underlying the evaluation of food images. Particularly, across two connected studies, Wolf et al (2018Wolf et al ( , 2019 found that subjects tended to gaze longer at images for which they felt uncertain about the evaluation, completely against the prevailing notion in the literature that "viewing leads to liking." Again, the finding of longer gazing at items that are not clearly liked or disliked can be interpreted in terms of volatility.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, this notion of extra information integration under doubt is also compatible with other findings from our laboratory on the cognitive mechanisms underlying the evaluation of food images. Particularly, across two connected studies, Wolf et al (2018Wolf et al ( , 2019 found that subjects tended to gaze longer at images for which they felt uncertain about the evaluation, completely against the prevailing notion in the literature that "viewing leads to liking." Again, the finding of longer gazing at items that are not clearly liked or disliked can be interpreted in terms of volatility.…”
Section: Discussionmentioning
confidence: 91%
“…Clarifying aspects of brain circuitry by illustrating the complex interplay between vision and cognition, 62 eye movement measurements are actively performed in interdisciplinary laboratories that integrate contributions from psychology, neuroscience, economy, philosophy and computer science. A vast number of efficient and well‐grounded behavioral experimental paradigms have been generated regarding sincerity, 63 magic‐tricks, 64, 65 judgmental tasks, 66–71 moral dilemma, 72 reading, 73–76 visual search, 77–79 gambling, 80 daily‐life activities, 81–86 problem‐solving, 39, 87–89 learning 90 and discrete choice in clinical decision‐making 91 . Vision science becomes actively adopted in neuromarketing, aiming to reveal valuable information about consumers’ decisions, as well as answer the question of how to hack the consumer's internal ‘purchase button’ 92–96 …”
Section: Vision Science As a New Practicementioning
confidence: 99%
“…Therefore, the gaze may not necessarily lead to more liking but contribute to the evaluative processing by integrating extra information. As Wolf et al (2019) suggested, the prolonged viewing time for the middle category may reflect doubt or uncertainty during the evaluative processing, potentially with an increased effort of information integration before reaching a conclusion.…”
Section: Discussionmentioning
confidence: 96%
“…This means that long gaze duration does not necessarily lead to a final purchase decision (see also Balcombe et al, 2017 ; Wolf et al, 2019 ). Wolf et al (2019) found that the relationship between gaze time and three options [i.e., the exclusive evaluation task contains rejection, deferment, and inclusion; the non-exclusive evaluation task contains 1 (“not at all”), 2 (neutral), and 3 (“very much”)] from participants who presented an inverted U-shaped trend. Therefore, the gaze may not necessarily lead to more liking but contribute to the evaluative processing by integrating extra information.…”
Section: Discussionmentioning
confidence: 99%